Mid-toned and high-toned elements in Yoruba - Oladiipo Ajiboye (LibraryPress@UF, 2007)
This paper examines three M-toned and three H-toned elements in Yoruba. On the one hand are the mid-toned mora (MT/-l), the mid-toned ni and the mid-toned ti. On the other hand are the H-toned mora (HT/-l), the H-toned nl and the H-toned 6. I propose that the parallels between these elements are syntactically and semantically conditioned. Every occurrence of a M-toned element shows agreement in the nominal domain whereas every occurrence of a H-toned element shows agreement in the verbal or extended verbal domain. I show that the pairs converge in their semantic role as case assigners. In particular, I claim that genitive Case assignment is carried out by the MT/-l or ti. I treat this as an instance of Case alternation. I further propose that when the two jointly assign genitive Case to the possessor, this is an instance of Case stacking.